2021
DOI: 10.1097/sap.0000000000002981
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Plastic Surgery Home Program Match Rates

Abstract: Background: Historically, integrated plastic surgery is one of the most competitive specialties in the residency match. In the 2020-2021 residency application cycle, plastic surgery programs were forced to adjust how they select applicants because of the COVID-19 pandemic disrupting visiting subinternships. We hypothesize that a higher proportion of plastic surgery applicants matched at their home institution during the 2020-2021 application cycle secondary to the implementation of COVID-19-related restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 13 publications
(31 reference statements)
2
25
0
Order By: Relevance
“…Our findings validated our hypothesis that a greater proportion of students applying for orthopaedics residency in 2021 would match at their home program compared with previous application cycles. These results mirror the findings of similar recent studies in plastic surgery, urology, otolaryngology, and dermatology 24-28 .…”
Section: Discussionsupporting
confidence: 91%
“…Our findings validated our hypothesis that a greater proportion of students applying for orthopaedics residency in 2021 would match at their home program compared with previous application cycles. These results mirror the findings of similar recent studies in plastic surgery, urology, otolaryngology, and dermatology 24-28 .…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies evaluating 2021 match data showed a significant increase in applicants matching at their home institutions compared with previous years. [8][9][10][11][12][13][14][15] The link between these changes and the COVID-19 pandemic has been described in detail. Among students interested in plastic surgery, COVID-19 not only affected the residency application process but also negatively impacted these students' confidence in their medical education.…”
Section: Introductionmentioning
confidence: 99%
“…2 Our findings were reinforced by multiple studies published following the 2021 plastic surgery match cycle, all supporting the conclusion that with changing interview structures and eliminating away sub-internships, rates of medical students matching at home institutions were significantly higher. 3 , 4 , 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%